1872 Wis. Sess. Laws 17, ch. 7, § 1, An Act to prohibit and prevent the carrying of concealed weapons. - (:unkn) unknown (My University, 1872)
If any person shall go armed with a concealed dirk, dagger, sword, pistol, or pistols, revolver, slung-shot, brass knuckles, or other offensive and dangerous weapon, he shall, on conviction thereof, be adjudged guilty of a misdemeanor
Keywords: CARRY - CONCEALED